Cho hàm số y = \frac{{ - {x^2} + 2x - 3}}{{x - 2}} . Đạo hàm y’ của hàm số là biểu thức nào sau đây?

Cho hàm số y = \frac{{ - {x^2} + 2x - 3}}{{x - 2}} . Đạo hàm y’ của hàm số là biểu thức nào sau đây?

A. - 1 - \frac{3}{{{{(x - 2)}^2}}} .

B. 1 + \frac{3}{{{{(x - 2)}^2}}} .

C. - 1 + \frac{3}{{{{(x - 2)}^2}}} .

D. 1 - \frac{3}{{{{(x - 2)}^2}}} .

Hướng dẫn giải

Đáp án C.

Ta có y' = \frac{{{{\left( { - {x^2} + 2x - 3} \right)}^\prime }\left( {x - 2} \right) - \left( { - {x^2} + 2x - 3} \right){{\left( {x - 2} \right)}^\prime }}}{{{{\left( {x - 2} \right)}^2}}} .
\begin{array}{l} = \frac{{\left( { - 2x + 2} \right)\left( {x - 2} \right) - \left( { - {x^2} + 2x - 3} \right).1}}{{{{\left( {x - 2} \right)}^2}}}\\ = \frac{{ - {x^2} + 4x - 1}}{{{{\left( {x - 2} \right)}^2}}} = - 1 + \frac{3}{{{{\left( {x - 2} \right)}^2}}} \end{array} .